Marketing Fish Smoke In The Market Langgam, Langgam Subsdistrict Pelalawan District Riau Province - M. Windra Fitra; Hamdi Hamid; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted by the 25th of April until 25 May 2016 in the Market Langgam, Langgam Subsdistrict Pelalawan District Riau Province. Research aims to analyze supply, demand and the form of marketing fish smoke in Langgam Market. Methods used in research is the method survey with the number of respondents 10 people. The number of supply and demand fish smoke the as many as 400 until 500 kg per week and when not the only about 150 until 200 kg per week. Marketing fish smoke from the products are good quality with a kind of fish Criptopterus bichirchis, Mystus nemurus, Pangasius pangasius, and Thynnichthys polylepis. Price of smoke in Market Langgam relatively accessible to the advantage Rp 5.000,- until Rp 10.000,- per kilogram. Distribution fish smoke in Market Langgam short enough, namely fishermen processing to intermediary traders then to the traders are a retailer until to consumers the end.Keywords: marketing, supply, demand, fish smoke, Langgam Market